The Role of the Family in the Education of Students - Mosinjonova Zebokhon Oybek kizi (Genius Publishing Group, 2022)
More and more of our young people are growing up in our society and contributing to the development of our country. The role of the family is very important for our young people to get a proper education, to live a happy life and achieve a lot. In this article, I talked about the role of the family, the role of parents, the importance of raising a child, the role of peace and tranquility in the family and of course, the upbringing of a child who is a mirror of the parents. After all, every young generation has a right to be happy.
Keywords: behavior; worldview; development; material